ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP PADA PROBLEM BASED LEARNING BERBANTUAN LKPD - Hia, Elvin Kartika; Harefa, Bilman Ariesta Nofaomasi; Harefa, Budizanolo; Hulu, Apriliani; Ziliwu, Seven Darma Putra; Mendrofa, Netti Kariani (Uninus Journal of Mathematics Education and Science (UJMES), 2026)
This study aims to describe the mathematical representation ability of eighth-grade junior high school students in Problem Based Learning (PBL) assisted by Student Worksheets (LKPD) on the topic of straight-line equations. The low mathematical representation ability of students became the background of this study, where students often experience difficulties in presenting mathematical ideas in various forms of representation. This study employed a quantitative descriptive design with samples selected using cluster random sampling technique, namely random selection of one class from all eighth-grade classes considered homogeneous, resulting in class VIII-A with 25 students at SMPN 1 Gunungsitoli Utara. The instrument used was a written description test consisting of 3 items covering three indicators: words or written text, visual representation, and equations or mathematical expressions. Categorization used the mean and standard deviation criteria based on Arikunto (2010). Results showed that students' mathematical representation ability was generally in the medium category with a mean of 71.33, maximum score of 83.33, and minimum score of 41.66. The words or written text indicator reached 52%, visual representation 60%, and equations or mathematical expressions 60% in the medium category. Thus, students' mathematical representation ability across all three indicators was predominantly in the medium category.